Biochemical recurrence of prostate cancer: initial results with (18F)PSMA-1007 PET/CT - Giesel, Frederik L.; Will, Leon; Kesch, Claudia; Freitag, Martin T.; Kremer, Christophe; Merkle, Jonas; Kiß, Oliver; Cardinale, Jens; Hadaschik, Boris; Hohenfellner, Markus; Kopka, Klaus; Haberkorn, Uwe; et al. (Journal of nuclear medicine, 2018)
Biochemical recurrence (BCR) is a concern for prostate cancer patients after local treatment. 68Ga-labeled prostate-specific membrane antigen (PSMA) ligands have significantly improved prostate cancer imaging. However, several 18F-labeled ligands that were developed as fluorinated tracers might present advantages. In this study, we analyzed the potential of 18F-PSMA-1007 in patients with BCR. Methods: Twelve patients with BCR after local treatment underwent PET/CT scans 1 and 3 h after injection of 18F-PSMA-1007. Results: 18F-PSMA-1007 PET/CT detected lesions in 9 of 12 patients (75%). A significant difference was observed when comparing the tracer uptake in 18F-PSMA-1007-positive lesions 1 and 3 h after injection (median SUVmax, 7.00 vs. 11.34; P < 0.001; n = 76). Forty-four (88%) of 50 18F-PSMA-1007-positive lymph nodes had a short-axis diameter of less than 8 mm. Conclusion: In this pilot study, 18F-PSMA-1007 PET/CT presented high potential for localization of recurrent disease in prostate cancer patients with BCR.
Gesehen am 05.04.2019
Die Zahl "18" ist im Titelzusatz hochgestellt